(untitled) (International journal of artificial intelligence, 2026)
This article examines the classification of negative words in English sentence structure and their syntactic and semantic functions. Negation is a fundamental linguistic category that affects meaning, polarity, and interpretation of sentences. The study aims to classify negative words in English based on their grammatical roles, structural positions, and interaction with sentence components. Through descriptive and analytical methods, negative words are grouped into several categories, including negative particles, pronouns, adverbs, determiners, and conjunctions. The findings demonstrate that negative words play a crucial role in shaping sentence structure and meaning, and their distribution follows specific grammatical rules in Modern English.